2015
DOI: 10.5709/acp-0168-4
|View full text |Cite
|
Sign up to set email alerts
|

Counterfactual Reasoning for Regretted Situations Involving Controllable Versus Uncontrollable Events: The Modulating Role of Contingent Self-Esteem

Abstract: We report a study that examined the modulating impact of contingent self-esteem on regret intensity for regretted outcomes associated with controllable versus uncontrollable events. The Contingent Self-Esteem Scale (e.g., Kernis & Goldman, 2006) was used to assess the extent to which a person’s sense of self-worth is based on self and others’ expectations. We found that there was an influence of self-esteem contingency for controllable but not for uncontrollable regret types. For controllable regret types indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Individual differences in a range of qualities (e.g., morality, self-enhancement, self-improvement, social desirability) seem also important, potentially functioning as moderators between regret and heroism, as the results of Study 3 suggest. In this regard, it should be noted that regret intensity seems to be associated with self-esteem contingency (i.e., instability, fragility), especially if the events involved seem controllable (Wilkinson et al, 2015). It might thus be worth examining whether, and under which conditions, self-esteem contingency can motivate people to engage in heroic acts when they experience regrets.…”
Section: Discussionmentioning
confidence: 99%
“…Individual differences in a range of qualities (e.g., morality, self-enhancement, self-improvement, social desirability) seem also important, potentially functioning as moderators between regret and heroism, as the results of Study 3 suggest. In this regard, it should be noted that regret intensity seems to be associated with self-esteem contingency (i.e., instability, fragility), especially if the events involved seem controllable (Wilkinson et al, 2015). It might thus be worth examining whether, and under which conditions, self-esteem contingency can motivate people to engage in heroic acts when they experience regrets.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, some studies on real life or career regrets have questioned the relationship between the intensity of regret and the controllability of the eliciting events. For example, Wilkinson et al (2015) found that while the level of regret for controllable events varied as a function of individual self-esteem, the one for uncontrollable events was always high. In the career domain, Wrzesniewski et al (2006) , Berg et al (2010) , and Newton et al (2012) found more intense regrets among those who had not chosen their current occupation, due to social or family constraints, than among those who had chosen it.…”
Section: Introductionmentioning
confidence: 99%
“…More recent studies similarly have often focused on the frequency with which participants’ regrets fall into particular categories or life domains (e.g., Roese et al, 2009; Morrison and Roese, 2011; but c.f. Wilkinson et al, 2015). Emotional frequency and intensity are distinct processes underlying the experience of affect (Diener et al, 1985; Schimmack and Diener, 1997) and they are not necessarily highly correlated: Frequent emotions (e.g., happiness) may not necessarily be intense, while infrequent emotions (e.g., rage) may be very intense.…”
Section: Introductionmentioning
confidence: 99%